Investigating the removal of linear alkyl benzene sulfonate from aqueous solution by ultraviolet irradiation and hydrogen peroxide process. Issue 32 (8th July 2016) - Ghaderpoori, Mansour; Dehghani, Mohammad Hadi
Abstract: This study investigated the efficiency of ultraviolet radiation and hydrogen peroxide for the removal of linear alkylbenzene sulfonate (LAS) from aqueous solutions. Methylene blue active substances assay and spectrophotometry were used to determine the amount of anionic and residual surfactants. The effect of H2 O2 concentration, initial concentration of surfactant, pH, and length of UV radiation were examined. The potential for use of UV/H2 O2 to degrade LAS was analyzed statistically using multiple linear regression analysis. The results showed that after 20 min of contact time, ultraviolet radiation alone removed 38.44% of the LAS. The use of hydrogen peroxide alone for 10, 20, and 30 min showed no effect on the removal of LAS. The removal rates for the combination UV/H2 O2 at 10, 20, and 30 min were 86.2, 90, and 96.5%, respectively. The results of this study showed that the use of ultraviolet radiation and hydrogen peroxide individually for degradation of anionic surfactant was not effective, but the combination of UV/H2 O2 was effective for the removal of anionic detergents.